Coconut Value Added At Tabongo District Gorontalo Regency - Indriani, Ria; Imran, supriyo (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
Tabongo District is one of the coconut production centers in Gorontalo Regency, with a total plantatio area of 982.88 Ha and a total production of 1.090.10 tons in 2019. The majority of farmer in this area sell coconut in the form of grains, yet other farmers process it into copra and coconut oil. The research aims to determine the marketing and the amount of added value of coconut which conducted for three months, September to November 2021, in Tabongo District. Purposive sampling of 20 farmers were applied as the sample utilizing the READSI (Rural Empowerment and Agricultural Development Scaling-up Initiative) program and the snowball sampling method to obtain four traders. This survey research method was consisted of primary and secondary data. Marketing analysis and Hayami value-added analysis are used to analyze data. The results showed that the processed form of coconut in Tabongo District is coconut grains, copra and coconut oil. There are three types of coconut marketing routes in the area: 1) copra farmers-wholesalers-Central Sulawesi, 2) coconut oil farmers-consumers, and 3) coconut farmers-traders-treatment factories. Every value added in 1 kg of copra product is Rp 1,150, or 49.92 percent of the product's worth. The profit rate for coconut copra processing is 46.13 percent of the product's value, which is Rp 2,400 per kg. Every added value in 1 kg of coconut oil product is Rp 5,246 or 45.05 percent of the product's worth. The profit rate of coconut oil treatment is 7.07 percent of the product's value, which is Rp 823 per kg. Meanwhile, the marketing added value obtained by coconut grain traders amounted to Rp 1,464.29 / kg or 54.23%.